Listener adapted Speech: How EFL Junior High School Students Adapt English Listening - Muhamad Sofian Hadi; Lidiyatul Izzah; Almira Faramadila Putri (Alsuna: Journal of Arabic and English Language, 2021)
Purpose - This study aims to determine whether the learning process with full English will be able to improve students' abilities in English skills more quickly. Design/methodology/approach - This research method is a qualitative method with a case study approach. This research was conducted in Malang. Researchers used junior high school students from grades 7 to 9 who have the same case for sampling. The method of data collection is by observation and a questionnaire containing ten statements. Then the authors analyzed the data using data reduction patterns, data presentation, and verification/conclusions. After that, the authors tabulated the data so that they could be described easily. Findings/result - The results of this study indicate that the use of full English in learning to listen to a procedural and a narrative text with gestures has positive opinions and perceptions from students, this also helps them find out some difficult vocabulary that is not yet known, helps students understand faster and last longer to remember vocabulary, besides that it also gives them the motivation to learn English. Originality/value - Optimistic and innovative teachers, are the keys to student success in improving English comprehension by listening to full English. Paper type – Research paper